Rapid detection of the beech leaf nematode, Litylenchus crenatae using recombinase polymerase amplification assay with lateral flow dipsticks - Mihail Kantor; Sergei A. Subbotin (PLoS ONE, 2026)
Beech leaf nematode, Litylenchus crenatae , is the causal agent of beech leaf disease (BLD), a condition characterized by interveinal dark-green banding, leaf thickening, bud abortion, and potentially tree mortality. Current identification methods for L. crenatae rely on morphometric analysis or molecular techniques such as conventional PCR and real-time PCR. To support timely management of BLD, there is a need for a rapid, field-deployable detection method. Recombinase polymerase amplification (RPA) is a new isothermal in vitro nucleic acid amplification technique that has been adopted for rapid and reliable diagnostics of nematodes. In this study, RPA assay combined with lateral flow (LF) dipsticks has been developed targeting the ITS rRNA gene of L. crenatae . The assay demonstrated high specificity, sensitivity, enabling direct detection from crude nematode extracts and from DNA leaf plant extracts. Assay specificity was validated against a range of non-target nematode species. The LF-RPA assay showed reliable detection within 28–30 min with a sensitivity of 0.002 nematode per reaction tube for crude nematode extracts or 0.03 nematode per reaction tube using DNA extracts from leaves. The LF-RPA assay presents a practical diagnostic tool for plant clinics and forestry professionals, enabling rapid on-site detection of L. crenatae in infested beech trees to support timely disease management decisions.